Iran's nuclear program and international law : from confrontation to accord - Joyner, Daniel (New York, NY : Oxford University Press, 2016)
This title provides an international legal analysis of the most important legal questions that have been raised since 2002 regarding Iran's nuclear program, and it sets those legal questions in their historical and diplomatic context. Its purpose is to clarify how the relevant sources of international law - including primarily the 1968 Nuclear Nonproliferation Treaty and International Atomic Energy Agency treaty law - should be properly applied in the context of the Iran case. It provides an instructional case study of the application of these sources of international law, the lessons which can be applied to inform both the ongoing legal and diplomatic dynamics surrounding the Iran nuclear dispute itself, as well as similar future cases.
This edition previously issued in print: 2016.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on August 9, 2016).
Keywords: Nuclear nonproliferation -- Iran; Politics and Government